La Constatación de los Bienes Físicos y su Influencia en los Inventarios Institucionales en el Gobierno Autónomo Descentralizado del Cantón Vinces 2022 - Mendoza Ochoa, Gabriela Gissell (2023)
The Municipal Decentralized Autonomous Governments are state institutions that are regulated by the Constitution of the Republic of Ecuador, the Organic Code of Territorial Organization, Autonomies and Decentralization (COOTAD). Like other state institutions, they must comply with the proper and responsible management of public resources or the Ecuadorian state; in such virtual the GAD make management using these resources through the goods. The main problems of assets and inventories in state institutions are related to the lack of knowledge on the part of public servants of their management and responsibility in their administration, among which we can mention: not knowing where they are, not knowing where they appeared, not knowing who has them, not knowing how much they are worth, not having the proper coding, not having delivery certificates and misusing the goods. The problems at the institutional level with regard to the control of public sector assets and inventories are mainly due to the absence of rules, attitude of servers and reconciliation of information. That is why this research project aims to determine the way in which the verification of physical goods influences the institutional inventories in the Decentralized Autonomous Government of the Vinces 2022 Canton. In this research project, the lists of property, plant and equipment, administrative control list, inventory list, end user assignments, physical verification report and physical taking schedule will be verified. The content of this project is divided into five chapters that are detailed below: chapter I corresponds to contextualization of the problem, chapter II to the theoretical framework, chapter III methodology, chapter IV results and discussion, chapter V conclusions and recommendations, finally, chapter VI bibliography.